Portraits of a few of the people I've made cry : stories - Sneed, Christine, 1971- (University of Massachusetts Press, 2010)
The ten stories in this striking debut collection examine the perils of love and what it means to live during an era when people will offer themselves, almost unthinkingly, to strangers. Risks and repercussions are never fully weighed. People leap and almost always land on rocky ground. May-December romances flourish in these stories, as do self-doubt and, in many cases, serious regret. Mysterious, dangerous benefactors, dead and living artists, movie stars and college professors, plagiarists, and distinguished foreign novelists are among the many different characters. No one is blameless, but villains are difficult to single out--everyone seemingly bears responsibility for his or her desires and for the outcome of difficult choices so often made hopefully and naively.